THE EFFECTS OF INCREASE IN PRODUCTION OF BIOFUELS ON WORLD AGRICULTURAL PRICES AND FOOD SECURITY - Figiel, Szczepan; Hamulczuk, Mariusz (European Scientific Journal, ESJ, 2014)
A rapid development of biofuels production observed all over the world in the recent decade has caused numerous consequences. Unfortunately, some of them have rather unexpectedly appeared to be not neutral to world food security. In the paper we briefly highlight key drivers of biofuels production and discuss some supporting as well as opposing arguments presented in the literature with regard to this development. Then, we focus on the transmission mechanism showing how increasing production of biofuels may influence agricultural markets and prices and eventually have an impact on food security. Finally, based on results of our own analysis using the World Bank and the FAO data we provide some empirical evidence that further policy driven development of the biofuels production can exacerbate its negative effects on food security. Especially, we point out emergence of visible linkages between energy and agricultural prices and underline increasing volatility of the latter ones. Due to market interconnectedness between biofuel and agro-food sectors, a strong increase in production of biofuels has contributed to higher levels and greater volatility of agricultural prices. As a result of such development, food affordability in many countries has lowered, hence, the overall world food security has worsened. In conclusion, to avoid distorting effects of biofuel policies, we recommend a flexible approach to the mandates including their removal since production of biofuels should compete for resources as being economically viable activity.